PENGUATAN BRAND IDENTITY HASEENA JEWELRY MELALUI BRAND STORYTELLING - Kharisma, Rizqi Sukma; Damastuti, Riski; Wardhana, Raditya; Andiyansari, Popi; Aisyah Nur Amini, Kofifa; Muthahari, Za’im; Ataraxia Dika, Mujahidin; Rafsanjani, Muhammad Isnaini Daffa (Jurnal Abdi Insani, 2025)
Kotagede silver crafts are a cultural heritage that has existed since the 17th century. Based on Yogyakarta City Regional Regulation Number 3 of 2015 concerning the Yogyakarta City Tourism Development Master Plan for 2015-2025, Kotagede is one of the regional tourism strategic areas. However, on the other hand, the number of silversmiths in Kotagede is decreasing. This is due to sales competition with imported casting products. So many craftsmen have switched professions to other sectors. This service activity was held to increase silversmiths' competitiveness in selling through social media. This service activity allows silversmiths to independently plan and create social media content for online marketing needs. Community service in copywriting training and social media management in the Kotagede silver craft home industry aims to enable partners to optimize their social media for online marketing needs. This event was held at the Grand Rohan Hotel, Bantul, DIY, on July 15, 2023. It was attended by community service partner participants, namely Haseena Jewelry, which focuses on marketing jewelry and silver craft products. This training presents resource persons from social media marketing practitioners. This training includes a greater understanding of creating engaging copywriting and social media management. The training results showed increased knowledge, as evidenced by the pretest and posttest scores. The average pretest score was 27.7, while the average posttest score was 77.3. This indicates that the participants' understanding before and after the training increased. In addition, the participants could plan and create social media content according to the intended segmentation. Participants can demonstrate a deeper understanding of copywriting and managing social media.